Tumor Ablation Using 3-Dimensional Electromagnetic-Guided Ultrasound Versus Standard Ultrasound in a Porcine Model. (August 2019) - Krasnick, Bradley Aaron; Sindram, David; Simo, Kerri; Goss, Ryan; Bharadwaj, Jeetendra; Howk, Kreg; Herdina, Katherine A.; Hammill, Chet W.
Introduction . The objective of this study was to compare the placement of ablation needles using 3-dimensional electromagnetic-guided ultrasound (guided) to standard ultrasound guidance (standard) in both laparoscopic surgery and open surgery. Endpoints for this study included targeting accuracy and number of required needle withdrawals and reorientations. Methods . Using a porcine model, fiducial markers were placed into the kidney and liver to represent tumors. Navigation and identification of target sites was achieved using standard or guided ultrasound. Intraprocedural observations as well as the number of needle placement attempts per target were recorded. Three board-certified general surgeons performed the navigation and ablation procedures. After completion of the navigation and ablation procedures, necropsy was performed. The position of the ablation zones relative to the fiducial markers was recorded. Results . A total of 48 procedures were performed across 6 animals (50% open and 50% laparoscopic). Overall, the guided ablations required 50% fewer attempts to successfully target the marker ( P = .01). There was a 62% reduction of attempts for guided laparoscopic ablation ( P = .006). On subgroup analysis of laparoscopic ablation, the benefit remained for liver ( P = .041) ablations, but not for renal ablations ( P = .093). There was no significant difference between the groups with regard to targeting accuracy (91.3% guided vs 95.4% standard, P = .58). Conclusions . The number of targeting attempts required during laparoscopic ablation procedures was significantly less with guided than with standard ultrasound, particularly for laparoscopic ablation of liver lesions. These findings suggest that the guided ultrasound can potentially reduce complications during laparoscopic ablation procedures.